Rusli Amran: Pioneer of Local History Research and His Contributions to the History of West Sumatra - Putri FY, Windri Augfensi; Husodo, Purwo (Faculty of Humanities, Andalas University, Padang, West Sumatra in cooperation with Kato Institute., 2024)
Rusli Amran, a Minangkabau intellectual born in Padang on September 14, 1922, has left numerous footprints in the intellectual world and Indonesian history. His works have indirectly but significantly shaped public understanding of past events, particularly in West Sumatra during the colonial era. Although Rusli Amran's contributions to Indonesian history are widely recognized, a more in-depth analysis of his intellectual framework and specific methodology used in his historical investigations is still needed. From the four significant events in West Sumatra (1981-1997), namely the arrival of the VOC in Padang, the Padri War, the Batipuh Rebellion, and the Three Unites: (Ombilin Coal Mine, Railway, and Teluk Bayur Harbor), Rusli Amran demonstrates that the four historical events during the Dutch colonial period in West Sumatra were interconnected. The main factor was the ease with which the people could be incited against each other. The Dutch colonial government exploited this main factor, which caused the people to be divided, and the indigenous people were easily manipulated, liked to be bribed, and prioritized power. Meanwhile, the Padris, who adhered to Islamic teachings, strongly disliked anything that was haram. This is what made the people of West Sumatra easily provoked. The Dutch colonial government also took advantage of this moment.